Hard carbon material, preparation method and alkali metal ion battery

By using hydrophilic solvents for swelling treatment and crosslinking reaction, the molecular structure of the hardcoat precursor is destroyed, a new pore structure is formed and the crosslinking reaction is promoted, which solves the problem of insufficient performance of hardcoat materials in the prior art, and improves structural stability and electrochemical performance.

CN119873789APending Publication Date: 2025-04-25CHINA COAL HUALI ENERGY HOLDINGS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510062553.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

It is difficult to prepare hard carbon materials with strong structural stability and excellent electrochemical performance in the prior art, and cannot meet the demand for high-performance negative electrode materials of sodium ion batteries and other alkali metal ion batteries.

Method used

The hydrophilic solvent is used as the swelling agent, and the hard carbon precursor is mixed with the swelling agent for swelling treatment, destroying the molecular structure of the aromatic hydrocarbons inside the coal, making the molecular structure loose, creating a new pore structure, promoting the progress of the crosslinking reaction, and forming a stable crosslinking network structure through the crosslinking agent and sintering treatment.

Benefits of technology

The structural modification of hard char material is achieved, the performance and performance consistency of the material is improved, the structural stability and electrochemical performance are enhanced, and it is suitable as a high-performance battery negative electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873789A_ABST
    Figure CN119873789A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon material, a preparation method and an alkali metal ion battery, and belongs to the technical field of battery materials. The preparation method comprises the following steps: firstly, mixing a hard carbon precursor with a swelling agent, sealing, performing swelling treatment, then mixing the swelling material with a cross-linking agent, and performing cross-linking reaction and sintering treatment. A hydrophilic solvent is used as a swelling agent, the hard carbon precursor is subjected to swelling treatment under specific conditions, molecules of the hydrophilic solvent and molecules of the hard carbon precursor interact with each other, the molecular structure of aromatic hydrocarbon in coal is destroyed, the originally compact molecular structure of the hard carbon precursor becomes loose, and the performance of the coal is improved. The preparation method is beneficial to subsequent cross-linking reaction and further optimization of the structure, and is also beneficial to generation of a new pore structure, so that active sites originally wrapped inside are exposed, the cross-linking reaction is further promoted, the reaction is more actively participated in the subsequent cross-linking reaction and other processes, and the reaction efficiency is improved. Therefore, the modification of the hard carbon precursor is more effectively realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a hard carbon material, a preparation method and an alkali metal ion battery. Background Art

[0002] Sodium-ion batteries, lithium-ion batteries, and potassium-ion batteries can be collectively referred to as "alkali metal ion batteries." Lithium, sodium, and potassium belong to the first main group and are called "alkali metals." The working principles of these three ion batteries are similar, relying on the movement of alkali metal ions (lithium ions, sodium ions, potassium ions) between the positive and negative electrodes to achieve charging and discharging. However, they have some differences in electrode materials, electrolytes, performance characteristics, and application scenarios. For example, lithium-ion batteries have high energy density and relatively short cycle life, and are widely used in portable electronic devices and electric vehicles; sodium-ion batteries have low cost and abundant resources, and are suitable for large-scale energy storage and other scenarios; potassium-ion batteries have high voltage operating potential and power density, and are expected to be used in the field of energy storage in the future.

[0003] However, due to some structural differences between lithium, sodium and potassium, the negative electrode materials of these three ion batteries are not completely universal. For example, sodium ion batteries are the most promising alternative to lithium ion batteries due to their abundant sodium resources, short charge and discharge time, good safety and wider applicable temperature range. + Ionic radius and higher standard electrochemical potential (2.71VNa / Na + and 3.04VLi / Li + vs. SHE) results in low power and energy density of sodium-ion batteries. In addition, due to the large ion size of sodium ions, graphite, the negative electrode material of commercial lithium-ion batteries, cannot effectively store sodium ions. At present, common negative electrode materials for sodium-ion batteries include carbon materials, alloys, oxides and organic compounds. Carbon materials have attracted more and more attention due to their low cost, high structural stability and good conductivity. Among them, hard carbon materials have become one of the first choices for negative electrode materials for sodium-ion batteries due to their high degree of disorder, large interlayer distance, and abundant nanopores and defects. And coal, as a hard carbon precursor, has a high carbon content and abundant resources. However, due to its excellent aromatic hydrocarbon structure, coal exhibits thermoplasticity during pyrolysis and is easy to form a graphite-like structure. At present, cross-linking agents or pre-oxidation methods are mostly used to modify coal to obtain hard carbon materials, but these methods still have shortcomings and it is still difficult to ensure the stability of the subsequent cross-linked structure.

[0004] Therefore, there is an urgent need to develop a new method to prepare hard carbon materials with excellent performance to meet the needs of sodium ion batteries and other alkali metal ion batteries for high-performance negative electrode materials and promote the further development of alkali metal ion battery technology. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide a hard carbon material with strong structural stability and excellent electrochemical performance, a preparation method and an alkali metal ion battery.

[0006] One of the purposes of the present invention is to provide a method for preparing a hard carbon material, the preparation method comprising the following steps: (1) mixing a hard carbon precursor and a swelling agent, sealing and then performing swelling treatment to obtain a swelling material; Wherein, the swelling agent is a hydrophilic solvent, the mass volume ratio of the hard carbon precursor and the swelling agent is 1g:(0.5-25)mL; the pressure of the swelling treatment is 0.1MPa-1.0MPa, the temperature of the swelling treatment is 20-90°C, and the total time of the swelling treatment is 1-24h; (2) The swelling material and the cross-linking agent are mixed to carry out a cross-linking reaction, and then sintered to obtain the hard carbon material.

[0007] Preferably, the hard carbon precursor includes one or more of bituminous coal, sub-bituminous coal or lignite.

[0008] Preferably, the particle size of the hard carbon precursor is D50≤20 μm.

[0009] Preferably, the hydrophilic solvent includes one or more of N-methylpyrrolidone, dimethylformamide, pyridine, tetrahydrofuran or methanol.

[0010] Preferably, during the swelling treatment: (a) stirring and ultrasonically treating the sealed mixture in sequence; (b) Repeat step (a) at least once; The total time of ultrasonic treatment is 2.5-6h.

[0011] Preferably, the cross-linking agent includes one or more of sucrose, glucose, starch, maleic anhydride, formaldehyde, ethylene glycol, itaconic acid, and phenol.

[0012] Preferably, the mass ratio of the swelling material to the cross-linking agent is 0.8-10:1.

[0013] Preferably, the cross-linking reaction is carried out under an inert atmosphere.

[0014] Preferably, the temperature of the cross-linking reaction is 300-400°C.

[0015] Preferably, the cross-linking reaction time is 1-10 hours.

[0016] Preferably, the sintering temperature is 800-1500°C.

[0017] Preferably, the sintering treatment time is 1-10 hours.

[0018] Preferably, in step (2), after the cross-linking reaction and before the sintering process, a step of ball milling the material is also included.

[0019] Preferably, the ball milling process is performed to a particle size D50 ≤ 10 μm.

[0020] A second object of the present invention is to provide a hard carbon material, which is prepared by the preparation method described above.

[0021] The third object of the present invention is to provide an alkali metal ion battery, wherein the negative electrode of the alkali metal ion battery includes the hard carbon material obtained by the preparation method as described above, and the alkali metal ion includes any one of a sodium ion battery, a lithium ion battery or a potassium ion battery. Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a hydrophilic solvent as a swelling agent. By mixing and swelling a hard carbon precursor with a hydrophilic solvent as a swelling agent under specific conditions, the hydrophilic solvent molecules interact with the hard carbon precursor molecules, which can destroy the aromatic hydrocarbon molecular structure inside the coal, and make the originally tight molecular structure of the hard carbon precursor loose, which is not only beneficial to the subsequent cross-linking reaction and further optimization of the structure, but also beneficial to the generation of a new pore structure, so that the active sites originally wrapped inside are exposed, thereby further promoting the cross-linking reaction, and more actively participating in the reaction in the subsequent cross-linking reaction and other processes, thereby more effectively achieving the structural modification of the hard carbon precursor and improving the performance of the material.

[0022] At the same time, the pore structure and loose molecular state produced by the swelling treatment greatly improve the transfer process of substances inside the hard carbon precursor. When other substances such as cross-linking agents are added later, these substances can diffuse more smoothly inside the hard carbon precursor and fully contact the active sites therein. This avoids the situation where local overreaction occurs while other parts do not react enough, allowing subsequent cross-linking reactions and other processes to occur more evenly inside the hard carbon precursor, which is conducive to the formation of a uniform cross-linked network structure, thereby improving the quality and performance consistency of hard carbon materials.

[0023] The preparation method of the present invention has important scientific value for the structure and process optimization of hard carbon materials for energy storage. The hard carbon materials prepared in this way have stable structure and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1This is a SEM image of the hard carbon material provided in Example 1; Figure 2 The charge and discharge curve of the sodium ion battery made from the hard carbon material provided in Example 1; Figure 3 The sodium storage cycle curve of the sodium ion battery made from the hard carbon material provided in Example 1. DETAILED DESCRIPTION

[0025] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details and with other methods, components, materials, etc.

[0026] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to".

[0027] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification are intended to include, in at least one embodiment, the specific referenced elements, structures or features described in connection with the embodiment. Thus, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. Furthermore, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.

[0028] According to a first aspect of the present invention, there is provided a method for preparing a hard carbon material, the method comprising the following steps: (1) mixing a hard carbon precursor and a swelling agent, sealing and then performing swelling treatment to obtain a swelling material; Wherein, the swelling agent is a hydrophilic solvent, the mass volume ratio of the hard carbon precursor and the swelling agent is 1g:(0.5-25)mL; the pressure of the swelling treatment is 0.1MPa-1.0MPa, the temperature of the swelling treatment is 20-90°C, and the total time of the swelling treatment is 1-24h; (2) The swelling material and the cross-linking agent are mixed to carry out a cross-linking reaction, and then sintered to obtain the hard carbon material.

[0029] In the present invention, in step (1), a hydrophilic solvent is used as a swelling agent. On the one hand, by mixing and swelling the hard carbon precursor with the hydrophilic solvent as a swelling agent under specific conditions, the hydrophilic solvent molecules interact with the hard carbon precursor molecules, which can destroy the aromatic molecular structure inside the coal, making the originally tight molecular structure of the hard carbon precursor loose, which is beneficial to the subsequent cross-linking reaction and further optimization of the structure; Secondly, it is also conducive to the generation of new pore structures, exposing the active sites originally wrapped inside, adding new active sites, and further promoting the cross-linking reaction, and more actively participating in the reaction in the subsequent cross-linking reaction, thereby more effectively achieving the structural modification of the hard carbon precursor and improving the performance of the material; Thirdly, the pore structure and loose molecular state produced by the swelling treatment greatly improve the transfer process of substances inside the hard carbon precursor. When other substances such as cross-linking agents are added later, these substances can diffuse more smoothly inside the hard carbon precursor and fully contact the active sites therein. This avoids the situation where local overreaction occurs while other parts underreact, allowing subsequent cross-linking reactions and other processes to occur more evenly inside the hard carbon precursor, which is conducive to the formation of a uniform cross-linked network structure, thereby improving the quality and performance consistency of hard carbon materials.

[0030] In step (2), during the cross-linking reaction, the swelling material is mixed with the cross-linking agent and a cross-linking reaction is carried out, which can form a stable cross-linked network structure between the molecules of the hard carbon precursor, effectively connecting the originally loose molecules together, and enhancing the structural stability of the hard carbon material; After further sintering treatment, the density and strength of the material can be improved, which makes the hard carbon material more conducive to withstanding the pressure and volume changes during the charging and discharging process as a negative electrode material of the battery, and can better maintain its shape and structural integrity, and reduce the pulverization and deformation of the material. During the sintering process, the atoms inside the hard carbon material after the swelling treatment and cross-linking reaction are easier to rearrange, thereby improving the crystal structure of the material. This helps to improve the conductivity, thermal stability and other properties of the material, making the hard carbon material more suitable as a high-performance negative electrode material for batteries or functional materials in other application scenarios.

[0031] The preparation method of the present invention has important scientific value for the structure and process optimization of hard carbon materials for energy storage. The hard carbon materials prepared in this way have stable structure and excellent electrochemical performance.

[0032] In the present invention, the hydrophilic solvent is used as a swelling agent, which can destroy the entanglement effect of the alkyl group, aromatic π-π interaction, weak hydrogen bond, strong hydrogen bond and hydrogen bond / π-π combination and other interactions between molecules more than the hydrophobic solvent.

[0033] In the present invention, the mass volume ratio of the hard carbon precursor and the swelling agent can be, for example, 1g:0.5mL, 1g:1mL, 1g:5mL, 1g:10mL, 1g:15mL, 1g:20mL or 1g:25mL, preferably 1g:(1-20)mL, and more preferably 1g:(5-12)mL.

[0034] In the present invention, if the mass-to-volume ratio of the hard carbon precursor and the swelling agent is too small, the solvent has a poor ability to weaken the hydrogen bonds and cross-linking effects between coal molecules, so the subsequent cross-linking and sodium storage performance are poor; if the mass-to-volume ratio of the hard carbon precursor and the swelling agent is too large, the swelling rate is too large, and the molecular structure of the condensed aromatic hydrocarbons is stripped, completely affecting the primary effect of the hard carbon.

[0035] In the present invention, the pressure of the swelling treatment may be, for example, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, or 1.0 MPa.

[0036] In the present invention, the appropriate pressure helps the solvent molecules to enter the coal pores and the interlamellar structure of the condensed aromatic hydrocarbon molecules.

[0037] In the present invention, the total time of the swelling treatment is 1-24 hours, for example, it can be 1 hour, 5 hours, 10 hours, 15 hours, 20 hours or 24 hours.

[0038] In the present invention, the temperature of the swelling treatment is 20-90°C, for example, it can be 20°C, 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 80°C, 85°C or 90°C.

[0039] In the present invention, if the temperature of the swelling treatment is too low, the fluidity of the solvent molecules is weak, which is not conducive to the solvent molecules entering the coal pore structure, preventing the expansion of the pores and inhibiting the escape of tar during the pyrolysis process; if the temperature of the swelling treatment is too high, the solvent evaporates too quickly, resulting in a defective pore structure that is too large, which is not conducive to the performance of the sodium storage performance.

[0040] The temperature of the swelling treatment is preferably 25-80°C.

[0041] When the swelling treatment temperature is 25-80°C, the solvent molecules have sufficient energy to penetrate into the internal structure of the hard carbon precursor, making it easier to break through the forces between the precursor molecules and enter the molecular gaps, thereby better interacting with the polar groups or aromatic structures in the precursor, thereby effectively destroying the intermolecular alkyl winding effect, aromatic π-π interaction, hydrogen bonding, etc., and promoting the swelling process.

[0042] Between 25 and 80°C, the solvent molecules can interact with the precursor molecules at an appropriate rate and strength, which can not only ensure the effective destruction of the internal structure of the precursor, but also avoid adverse effects caused by excessively high temperature.

[0043] In a preferred embodiment of the present invention, the hard carbon precursor includes one or more of bituminous coal, sub-bituminous coal or lignite.

[0044] Preferably, the particle size of the hard carbon precursor is D50≤20 μm, for example, 20 μm, 18 μm, 16 μm, 14 μm, 12 μm or 10 μm.

[0045] In the present invention, during the swelling process of the hard carbon precursor with a particle size of D50≤20μm, the solvent molecules can contact the surface of the precursor particles more quickly and fully, and then penetrate into the internal structure of the particles more effectively. This helps to speed up the swelling reaction, so that the molecular structure inside the precursor can be destroyed in a shorter time, produce a new pore structure and expose more active sites, and provide better conditions for subsequent steps such as cross-linking reactions, thereby improving the preparation efficiency of the entire hard carbon material. It is also beneficial to achieve more uniform structural modification during swelling and subsequent reactions. When the particle size is small, the effects on each particle and between particles during swelling, cross-linking and other reactions are closer, which can reduce the local reaction unevenness caused by differences in particle size.

[0046] In a preferred embodiment of the present invention, the hydrophilic solvent includes one or more of N-methylpyrrolidone, dimethylformamide, pyridine, tetrahydrofuran or methanol, for example, it can be N-methylpyrrolidone, dimethylformamide, pyridine, tetrahydrofuran, methanol, N-methylpyrrolidone and dimethylformamide, N-methylpyrrolidone and tetrahydrofuran, or a combination of N-methylpyrrolidone, dimethylformamide and tetrahydrofuran.

[0047] Preferably, the hydrophilic solvent is a combination of any two of N-methylpyrrolidone, dimethylformamide, pyridine, tetrahydrofuran or methanol.

[0048] Preferably, the hydrophilic solvent comprises tetrahydrofuran and N-methylpyrrolidone, and the volume ratio of tetrahydrofuran to N-methylpyrrolidone is 0.5-2:1, for example, it can be 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.7:1 or 2:1, preferably 1:1.

[0049] The combination of tetrahydrofuran and N-methylpyrrolidone in an appropriate ratio can fully achieve synergistic coordination and can selectively destroy the intermolecular alkyl winding effect, aromatic π-π interaction, weak hydrogen bond, strong hydrogen bond and hydrogen bond / π-π binding interactions.

[0050] In a preferred embodiment of the present invention, during the swelling process: (a) stirring and ultrasonically treating the sealed mixture in sequence; (b) repeating step (a) at least once, for example, once, five times, seven times, eight times, or ten times; The total time of ultrasonic treatment is 2.5-6h.

[0051] In the present invention, the steps of stirring and ultrasonic treatment are helpful to make the hard carbon precursor swell better.

[0052] Preferably, during the swelling treatment in step (1), the total time of ultrasonic treatment is 2.5-6 h, for example, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h.

[0053] In a preferred embodiment of the present invention, the cross-linking agent includes one or more of sucrose, glucose, starch, maleic anhydride, formaldehyde, ethylene glycol, itaconic acid, and phenol.

[0054] Preferably, the mass ratio of the swelling material to the cross-linking agent is (0.8-10):1, for example, it can be 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.

[0055] In the present invention, if the mass ratio of the swelling material to the cross-linking agent is too low, the carbon layers are mostly rearranged in an orderly manner, resulting in a small interlayer spacing of the carbon material, a low degree of disorder, and a small amount of pore structure; if the mass ratio of the swelling material to the cross-linking agent is too high, the interlayer spacing is too large, and the excessive pore structure caused by too much cross-linking agent is often not conducive to sodium storage.

[0056] Preferably, in step (2), the swelling material and the cross-linking agent are mixed together by grinding, that is, the swelling material and the cross-linking agent are subjected to a ball milling mixing treatment.

[0057] Preferably, the cross-linking reaction is carried out under an inert atmosphere, and the gas in the inert atmosphere may be, for example, argon and / or nitrogen.

[0058] In a preferred embodiment of the present invention, the temperature of the cross-linking reaction is 300-400°C, for example, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C.

[0059] Preferably, the cross-linking reaction time is 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0060] Preferably, after the swelling material and the cross-linking agent are mixed, an inert gas with a flow rate of 100-200 mL / min (for example, 100 mL / min, 120 mL / min, 140 mL / min, 160 mL / min, 180 mL / min or 200 mL / min, etc.) is introduced to form an inert atmosphere, and then the temperature is increased to 300-400° C. at a heating rate of 1-2° C. / min to carry out a cross-linking reaction for 1-10 hours.

[0061] Preferably, the heating rate is 2°C / min.

[0062] In a preferred embodiment of the present invention, the temperature of the sintering treatment is 800-1500°C, for example, it can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C.

[0063] Preferably, the sintering treatment time is 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0064] Preferably, the sintering process is performed in an inert atmosphere, and the gas in the inert atmosphere may be, for example, argon and / or nitrogen.

[0065] In a preferred embodiment of the present invention, in step (2), after the cross-linking reaction and before the sintering treatment, the material is further subjected to ball milling treatment, wherein the ball milling treatment is performed to a particle size D50 ≤ 10 μm, for example, 10 μm, 8 μm, 6 μm, 4 μm, 2 μm or 1 μm.

[0066] In a preferred embodiment of the present invention, the preparation method comprises the following steps: (1) Coal powder with a particle size of D50 ≤ 20 μm is mixed with a hydrophilic solvent, and after sealing, it is stirred and ultrasonically treated in sequence under the conditions of a pressure of 0.1 MPa-1.0 MPa and a temperature of 25-80°C, and the stirring and ultrasonic treatment are repeated at least once. The total time of the swelling treatment is 1-24 hours, and the total time of the ultrasonic treatment is 2.5-6 hours. After the end, a solid-liquid mixture is obtained, which is then dried to obtain a swelling material.

[0067] The mass volume ratio of the coal-like substance to the hydrophilic solvent is 1 g:(1-20) mL.

[0068] (2) The swelling material and the cross-linking agent are ball-milled in a mass ratio of (0.8-10):1, and then an inert gas is introduced at a flow rate of 100-200 mL / min to form an inert atmosphere, and a cross-linking reaction is carried out at 300-400°C for 1-10 h, and then ball-milled to a particle size D50 ≤ 10 μm, and then sintered at 800-1500°C for 1-10 h under an inert atmosphere to obtain the hard carbon material.

[0069] The cross-linking agent and the hydrophilic solvent are of different types, and the cross-linking agent includes sucrose, glucose, starch, maleic anhydride, formaldehyde, ethylene glycol, itaconic acid, and phenol.

[0070] In a second aspect, the present invention provides a hard carbon material, which is prepared by the preparation method described in the first aspect.

[0071] In a third aspect, the present invention provides an alkali metal ion battery, wherein the alkali metal ion battery is any one of a sodium ion battery, a lithium ion battery or a potassium ion battery, and the negative electrode material of the alkali metal ion battery includes the hard carbon material described in the second aspect.

[0072] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0073] Example The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0074] In the following examples, unless otherwise specified, all raw materials are commercially available products.

[0075] Example 1 This embodiment provides a method for preparing a hard carbon material, the preparation method comprising the following steps: (1) 5 g of bituminous coal powder with a particle size D50 of 20 μm was mixed with 20 mL of tetrahydrofuran, and the mixture was sealed and stirred for 30 min and ultrasonically treated for 30 min at a pressure of 0.2 MPa and a temperature of 60°C. The mixture was repeated 8 times. The total swelling time was 8 h and the total ultrasonic treatment time was 4 h. After the mixture was completed, a solid-liquid mixture was obtained, which was then placed in a water bath for drying to obtain a swelling material. The mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:8 mL; (2) The swelling material and sucrose are ball-milled at a mass ratio of 7:3 for 30 minutes, and then pressed into tablets and introduced with argon gas at a flow rate of 150 mL / min to create an inert atmosphere. The temperature is raised to 350°C at a heating rate of 2°C / min, and a cross-linking reaction is carried out for 2 hours to obtain a black flaky solid. The solid is then ball-milled to a particle size D50 of 10 μm, and then sintered at a temperature of 1300°C in an argon atmosphere for 2 hours. After the sintering, it is cooled to room temperature to obtain the hard carbon material.

[0076] Example 2 The difference between this embodiment and embodiment 1 is that the swelling agent is a combination of N-methylpyrrolidone and dimethylformamide, and the volume ratio of N-methylpyrrolidone to dimethylformamide is 1:1.

[0077] The remaining preparation methods and parameters are the same as those in Example 1.

[0078] Example 3 The difference between this embodiment and embodiment 1 is that the swelling agent is a combination of tetrahydrofuran and N-methylpyrrolidone, and the volume ratio of tetrahydrofuran to N-methylpyrrolidone is 1:1.

[0079] The remaining preparation methods and parameters are the same as those in Example 1.

[0080] Example 4 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:0.5 mL.

[0081] The remaining preparation methods and parameters are the same as those in Example 1.

[0082] Example 5 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:1 mL.

[0083] The remaining preparation methods and parameters are the same as those in Example 1.

[0084] Example 6 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:5 mL.

[0085] The remaining preparation methods and parameters are the same as those in Example 1.

[0086] Example 7 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:12 mL.

[0087] The remaining preparation methods and parameters are the same as those in Example 1.

[0088] Example 8 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:20 mL.

[0089] The remaining preparation methods and parameters are the same as those in Example 1.

[0090] Example 9 The difference between this embodiment and embodiment 1 is that the mass volume ratio of bituminous coal and tetrahydrofuran is 1 g:25 mL.

[0091] The remaining preparation methods and parameters are the same as those in Example 1.

[0092] Example 10 The difference between this embodiment and embodiment 1 is that the temperature of the swelling treatment in step (1) is 20°C.

[0093] The remaining preparation methods and parameters are the same as those in Example 1.

[0094] Embodiment 11 The difference between this embodiment and embodiment 1 is that the temperature of the swelling treatment in step (1) is 25°C.

[0095] The remaining preparation methods and parameters are the same as those in Example 1.

[0096] Example 12 The difference between this embodiment and embodiment 1 is that the temperature of the swelling treatment in step (1) is 80°C.

[0097] The remaining preparation methods and parameters are the same as those in Example 1.

[0098] Embodiment 13 The difference between this embodiment and embodiment 1 is that the temperature of the swelling treatment in step (1) is 90°C.

[0099] The remaining preparation methods and parameters are the same as those in Example 1.

[0100] Embodiment 14 The difference between this embodiment and embodiment 1 is that the mass ratio of the swelling material to sucrose in step (2) is 5:6.

[0101] The remaining preparation methods and parameters are the same as those in Example 1.

[0102] Embodiment 15 The difference between this embodiment and embodiment 1 is that the mass ratio of the swelling material to sucrose in step (2) is 10:1.

[0103] The remaining preparation methods and parameters are the same as those in Example 1.

[0104] Example 16 The difference between this embodiment and embodiment 1 is that the atmosphere for the cross-linking reaction and sintering treatment in step (2) is a nitrogen atmosphere.

[0105] The remaining preparation methods and parameters are the same as those in Example 1.

[0106] Embodiment 17 The difference between this embodiment and embodiment 1 is that the heating rate of the cross-linking reaction in step (2) is 1°C / min.

[0107] The remaining preparation methods and parameters are the same as those in Example 1.

[0108] Comparative Example 1 The difference between this comparative example and Example 1 is that dichloromethane is used as the swelling agent in step (1).

[0109] The remaining preparation methods and parameters are the same as those in Example 1.

[0110] Performance Testing 1. The microstructure of the hard carbon material prepared in Example 1 is characterized, and its SEM image is as follows: Figure 1 shown.

[0111] 2. The hard carbon materials provided in the above embodiments and comparative examples are made into negative electrode sheets, and assembled with positive electrode sheets, separators and electrolytes to obtain sodium ion button batteries. The specific steps include: A slurry made by mixing hard carbon material, conductive carbon black Super P, 1.5% carboxymethyl cellulose (CMC) and 45% styrene-butadiene rubber (SBR) in a mass ratio of 91:2:2:5 was coated on copper foil. The counter electrode was metallic sodium. Glass fiber (Whatman, GF / D) and 1 M NaClF6 were used as separator and electrolyte, respectively. CR2032 button cells were assembled in a glove box (H2O, O2 < 0.1 ppm). Charge and discharge tests at 0-2 V as well as cycle stability tests were performed using a LAND CT2001 battery tester (LAND, Wuhan, China).

[0112] The above sodium ion batteries were subjected to capacity performance tests and cycle stability tests.

[0113] The conditions for the capacity performance test are: charging and discharging at a current of 30mA / g, and the voltage window is set to 0-2V.

[0114] The conditions for the cycle stability test are: charge and discharge the button at a current of 30 mA / g for 3 cycles, and then charge and discharge at a current density of 100 mA / g. The current window is set to 0-2 V and the number of cycles is 150.

[0115] The charge and discharge curve of the sodium ion battery made of the hard carbon material provided in Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the sodium ion battery has a reversible capacity of about 304 mAh / g.

[0116] The sodium storage cycle curve of the sodium ion battery made of the hard carbon material provided in Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that the capacity retention rate of the sodium ion battery is still greater than 90% after 150 cycles.

[0117] The test results of the reversible capacity and capacity retention rate of Examples 1-17 and Comparative Example 1 are shown in Table 1.

[0118] Table 1 Reversible capacity and capacity retention rate of Examples 1-17 and Comparative Example 1

[0119] As can be seen from the above table, the present invention uses a hydrophilic solvent as a swelling agent, and through simple control means, not only achieves structural modification and high-value utilization of hard carbon precursors, but also destroys the aromatic molecular structure inside coal, effectively promotes the occurrence of coal cross-linking, and enhances the stability of subsequent cross-linked structures. This method has important scientific value for the structural and process optimization of hard carbon materials for energy storage. The hard carbon material prepared based on this has a stable structure and excellent electrochemical properties.

[0120] It can be seen from Example 1 and Examples 4-9 that if the mass-to-volume ratio of the hard carbon precursor and the swelling agent is too small, the solvent has a poor ability to weaken the hydrogen bonds and cross-linking effects between coal molecules, so the subsequent cross-linking and sodium storage performance are poor; if the mass-to-volume ratio of the hard carbon precursor and the swelling agent is too large, the swelling rate is too large, and the molecular structure of the condensed aromatic hydrocarbons is stripped, completely affecting the initial effect of the hard carbon.

[0121] It can be seen from Examples 1 and 10-13 that if the temperature of the swelling treatment is too low, the fluidity of the solvent molecules will be slowed down, which is not conducive to the solvent molecules entering the coal pores and the interlamellar structure of the condensed aromatic hydrocarbon molecules, preventing the expansion of the pores and the interlamellar structure, and inhibiting the escape of tar during the pyrolysis process; if the temperature of the swelling treatment is too high, the solvent will evaporate too quickly, resulting in a defective pore structure that is too large, which is not conducive to the performance of the sodium storage performance.

[0122] It can be seen from Example 1 and Examples 14-15 that if the mass ratio of the swelling material to the cross-linking agent is too low, the carbon layers are mostly rearranged in an orderly manner, resulting in a small interlayer spacing of the carbon material, a low degree of disorder, and less pore structure; if the mass ratio of the swelling material to the cross-linking agent is too high, the interlayer spacing is too large, and the excessive pore structure caused by excessive cross-linking agent is often not conducive to sodium storage.

[0123] It can be seen from Example 1 and Comparative Example 1 that if the hydrophilic solvent is replaced with a hydrophobic solvent, the solvent has poor solubility for condensed ring compounds and cannot dissolve more substances, which is not conducive to subsequent cross-linking; the solvent has poor ability to weaken the hydrogen bonds and cross-linking effects between coal molecules, and has poor damage to the coal structure. The carbon layer is easily rearranged in an orderly manner during the carbonization process.

[0124] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: The preparation method comprises the following steps: (1) mixing a hard carbon precursor and a swelling agent, sealing and then performing swelling treatment to obtain a swelling material; Wherein, the swelling agent is a hydrophilic solvent, the mass volume ratio of the hard carbon precursor and the swelling agent is 1g:(0.5-25)mL; the pressure of the swelling treatment is 0.1MPa-1.0MPa, the temperature of the swelling treatment is 20-90°C, and the total time of the swelling treatment is 1-24h; (2) The swelling material and the cross-linking agent are mixed to carry out a cross-linking reaction, and then sintered to obtain the hard carbon material.

2. The preparation method according to claim 1, characterized in that: The hard carbon precursor includes one or more of bituminous coal, sub-bituminous coal or lignite, and the particle size of the hard carbon precursor is D50≤20 μm.

3. The preparation method according to claim 1, characterized in that: The hydrophilic solvent includes one or more of N-methylpyrrolidone, dimethylformamide, pyridine, tetrahydrofuran or methanol.

4. The preparation method according to claim 1, characterized in that: During the swelling process: (a) stirring and ultrasonically treating the sealed mixture in sequence; (b) Repeat step (a) at least once; The total time of ultrasonic treatment is 2.5-6h.

5. The preparation method according to claim 1, characterized in that: The cross-linking agent includes one or more of sucrose, glucose, starch, maleic anhydride, formaldehyde, ethylene glycol, itaconic acid, and phenol; The mass ratio of the swelling material to the cross-linking agent is 0.8-10:

1.

6. The preparation method according to claim 1, characterized in that: The cross-linking reaction is carried out under an inert atmosphere, the temperature of the cross-linking reaction is 300-400° C., and the time of the cross-linking reaction is 1-10 h.

7. According to claim 1, it is characterized in that The sintering temperature is 800-1500° C., and the sintering time is 1-10 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (2), after the cross-linking reaction and before the sintering process, the material is subjected to ball milling to a particle size of D50 ≤ 10 μm.

9. A hard carbon material, characterized in that: The hard carbon material is prepared by the preparation method according to any one of claims 1 to 8.

10. An alkali metal ion battery, characterized in that: The negative electrode of the alkali metal ion battery includes the hard carbon material as claimed in claim 9, and the alkali metal ion includes any one of a sodium ion battery, a lithium ion battery or a potassium ion battery.